Play behaviour in Urial (Ovis orientalis bocharensis) lamb - Guanyabens Garrido, Irene (2018)
Welfare constitutes of health, physiology, behaviour and reproduction. It becomes very important when a species suffers in any of these parameters and thus, the assessment of welfare should be carried out. Play behaviour has been identified as a positive behaviour performed when satisfactory circumstances are present. In order to assess welfare through play in domesticated animals it is essential to know the natural behaviour of the ancestral species. The purpose of this study was to evaluate and describe the ontogeny of play behaviour in Urial sheep lambs, the ancestor of our domesticated sheep, during their first weeks of life. With this, also to contribute in the conservation of this vulnerable mountain ungulate and the maintaining of its predator-prey relationship.